MORPHOLOGICAL ERRORS IN STUDENTS’ WRITING RECOUNT TEXT OF JUNIOR HIGH SCHOOL 18 BATANGHARI - Faiqah Mahmudah; Rahmatika, Yulia (JR-ELT (Journal of Research in English Language Teaching), 2021)
The aim of this study was to find out morphological errors made by students of SMP Negeri 18 Batanghari in writing recount text. This is descriptive qualitative research, the data were collected by documentation and analysed by Surface Strategy Taxonomy. This research revaled that there are four types of errors with the total number 58 errors made by the students in writing recount text. Omission error which consists of three categories of omission errors i.e. omission of plural, auxiliary verb, gerund, with the total number of errors are 8 or 13,56%, addition error includes four categories of addition errors i.e. addition of gerund, plural, pronoun, noun, with the total number of errors are 8 or 13,56%, misformation error that consist of misformation error of tense with the total number of errors are 38 or 66,10%, and the last misordering error that consist of misordering of spelling with the total number of errors are 4 or 6,78%.